1988
DOI: 10.1148/radiology.168.3.3043545
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal and transabdominal sonography: prospective comparison.

Abstract: Transvaginal (TV) and transabdominal (TA) sonography were compared in a prospective study. A total of 230 examinations (126 pelvic, 104 pregnancy) were performed on 215 patients, ranging in age from 14 to 80 years. The improved anatomic detail on TV scans yielded new information in 138 (60%) examinations and better visualization of pelvic structures in 51 (22%) examinations. There was no important difference in diagnostic information provided by the two imaging modalities in 36 (16%) cases, and TV images were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
2

Year Published

1990
1990
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(29 citation statements)
references
References 0 publications
3
24
0
2
Order By: Relevance
“…5 Most practitioners, therefore, recommend a combination of transabdominal and transvaginal scanning, since the transvaginal approach will give better detail of the pelvic organs, but the transabdominal approach will provide clear information about large pelvic masses or fibroids difficult to see transvaginally due to the limited field of view. [1][2][3][4][5] We agree with the results described above in that the transabdominal scan cannot be abandoned completely in favor of the transvaginal approach. Surely, 34 of 206 patients (16.5%) required a transabdominal scan to visualize the pelvis adequately in our study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…5 Most practitioners, therefore, recommend a combination of transabdominal and transvaginal scanning, since the transvaginal approach will give better detail of the pelvic organs, but the transabdominal approach will provide clear information about large pelvic masses or fibroids difficult to see transvaginally due to the limited field of view. [1][2][3][4][5] We agree with the results described above in that the transabdominal scan cannot be abandoned completely in favor of the transvaginal approach. Surely, 34 of 206 patients (16.5%) required a transabdominal scan to visualize the pelvis adequately in our study.…”
Section: Discussionsupporting
confidence: 90%
“…[1][2][3][4] Tessler and colleagues showed that the transvaginal study was superior in 60% of patients, equal in another 36%, and inferior in only four patients (3.7%) compared with the transabdominal scan. 1 Leibman and coauthors also reported that more information was obtained from a transvaginal scan than from a transabdominal scan in 76% of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of higher frequency transducers improves spatial resolution and reduces imaging artefacts. It has been well established that the greater resolution afforded by EVS renders it invaluable in the work-up of multiple gynecological disorders (Coleman et al, 1988;Timor-Tritsch et al, 1988;Lyons et al, 1992).…”
Section: Endovaginal Sonographymentioning
confidence: 99%
“…Growth of the dominant follicle is generally mentioned to be linear, with a mean daily growth rate around 2-3 mm (163, 183). Since 1985 the transvaginal route has been introduced for pelvic ultrasound (202,203), allowing enhanced imaging resolution and a more reliable assessment of changes in number and size of small follicles (197). Growth of dominant and nondominant follicles has been studied extensively by our group using transvaginal sonography (TVS) (for review see Refs.…”
Section: February 1997mentioning
confidence: 99%